The hundred secret senses - Tan, Amy 1952- (Putnam, 1995)
The story of two sisters, one brought up in the U.S., the other in China. The American sister is contemptuous of the other's belief in ghosts until events cause her to understand what they can do. A tale of two cultures by the author of The Kitchen God's Wife.
Keywords: Chinese American women -- Fiction; Domestic fiction.; Sisters -- United States -- Fiction; USA; Fiktionale Darstellung; Domestic fiction